Repairing 2024 Aluminum Alloy via Electrospark Deposition Process: A Feasibility Study. (27th March 2018) - Renna, G.; Leo, P.; Casalino, G.; Cerri, E.
Abstract : The electrospark deposition (ESD) technique has been studied as a potential method to repair locally damaged 2024 rolled sheets supplied in natural-aged (T4) and artificial-aged (T6) conditions. The 2024-T4 and 2024-T6 tensile samples were first notched, and then the notches were filled (repaired) by ESD with the same aluminum alloy. The effect of process parameters on the microstructure of the filling material and the substrate properties was studied by optical and scanning electron microscopy. Tensile and hardness tests were performed. The tensile test showed that T4 and T6 as-repaired specimens had low tensile properties, which was due to defectiveness and residual stress caused by high cooling rate during reparation. However, the as-repaired specimens were heat-treated at either 135°C or 190°C to improve the mechanical properties. A better yield strength was observed for the T4 heat-treated alloy. The ductility and ultimate tensile strength did not change, being mainly affected by voids and microcracks.